A Novel Technique to Lengthen the Reverse Latissimus Dorsi Muscle Flap Arc. Issue 7 (15th July 2021) - Takanari, Keisuke; Nakamura, Yutaka; Uchibori, Takafumi; Nakamura, Ryota; Ebisawa, Katsumi; Kambe, Miki; Urakawa, Hiroshi; Nishida, Yoshihiro; Kamei, Yuzuru
Abstract : Summary: Reconstruction of the lower lumbar region is challenging for surgeons due to limited locoregional flap choices. The latissimus dorsi muscle flap is a mainstay for this area; however, there are several limitations, including that the dominant thoracodorsal artery and vein pedicle-based flaps are not reachable for reconstruction of the lumbar region, while perforator of intercostal artery and veins pedicle-based reverse latissimus dorsi (RLD) flap mobility is limited by including multiple perforators. Here, we describe a novel operative technique that lengthens the rotation arc of RLD muscle flaps. The surgical technique is as follows: RLD is elevated based on lower perforator of intercostal artery and veins (usually including two of the eighth–11th perforators); thoracodorsal artery and vein are ligated; and the flap is mobilized toward the defect. When RLD was not reachable to the defect, the far aspect of the intercostal artery and vein from the defect was ligated and the perforator was elevated with the near aspect of the intercostal artery and vein from intercostal space. Because the intercostal space measured between approximately 3 cm and 4 cm, this dissection gained 3–4 cm of rotational arc per intercostal space. Moreover, because the lower ribs follow a medio-cranial to latero-caudal direction, this dissection enabled the flap to extend latero-caudally or medio-cranially while maintaining its blood supply. Other applications using this technique may involve expanding the RLD flap arc caudally, ventrally, and ipsilaterally. We believe this new technique provides a reliable alternative for lower back reconstruction.